PENGARUH KONTRAK PSIKOLOGIS DAN PSYCHOLOGICAL WELL BEING TERHADAP KINERJA KARYAWAN : STUDI PADA PT ASIA KAPITALINDO JAKARTA - DEVY SOFYANTY; TOPAN SETIAWAN (KULTURA DIGITAL MEDIA ( Research and Academic Publication Consulting ), 2020)
psychological well being partially or simultaneously on employee performance. The research was conducted at PT Asia Kapitalindo Jakarta. The research method uses quantitative methods ,, the sampling technique used is a census. Data collection techniques used interviews and questionnaires, while data analysis used multiple linear regression. Based on the analysis results, the following findings were obtained: (1) simultaneously psychological contract and psychological well being positive and significant effect on employee performance, (2) partially psychological contract positive and significant effect on employee performance, (3) partially psychological well being positive and significant effect on employee performance.